2012
DOI: 10.1021/es3030148
|View full text |Cite
|
Sign up to set email alerts
|

Global Synthesis and Critical Evaluation of Pharmaceutical Data Sets Collected from River Systems

Abstract: Pharmaceuticals have emerged as a major group of environmental contaminants over the past decade but relatively little is known about their occurrence in freshwaters compared to other pollutants. We present a global-scale analysis of the presence of 203 pharmaceuticals across 41 countries and show that contamination is extensive due to widespread consumption and subsequent disposal to rivers. There are clear regional biases in current understanding with little work outside North America, Europe, and China, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
394
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 663 publications
(431 citation statements)
references
References 208 publications
13
394
3
7
Order By: Relevance
“…According to the literature reviewed here, it is clear that antidepressants, psychiatric drugs (benzodiazepines) and antihistamines can induce behavioural changes in fish at concentrations ranging from low ng l 21 to low mg l 21 [33,36,42,49], which are close to the concentrations found in natural systems [21,29]. Although this suggests that ecological effects of pharmaceuticals may occur in aquatic systems dominated by wastewater effluent, effects of some pharmaceuticals were found only at higher, not environmentally relevant, concentrations.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…According to the literature reviewed here, it is clear that antidepressants, psychiatric drugs (benzodiazepines) and antihistamines can induce behavioural changes in fish at concentrations ranging from low ng l 21 to low mg l 21 [33,36,42,49], which are close to the concentrations found in natural systems [21,29]. Although this suggests that ecological effects of pharmaceuticals may occur in aquatic systems dominated by wastewater effluent, effects of some pharmaceuticals were found only at higher, not environmentally relevant, concentrations.…”
Section: Discussionsupporting
confidence: 59%
“…Absolute recoveries of oxazepam in the damselfly and fish muscle extraction were 104% (RSD 7%, N ¼ 6) and 100% (RSD 12%, N ¼ 6), respectively. Limit of quantification was 0.5 mg kg 21 . Bioconcentration factors (BCFs) were estimated by dividing individual full body concentrations with measured water concentration in the corresponding individual aquarium.…”
Section: (B) Water and Tissue Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…Contaminants of emerging concern (CECs), including pharmaceuticals and personal care products 42 (PPCPs), drugs of abuse (DOAs), hormones and stimulants are present in the aquatic environment 43 (Blair et al, 2013a;Hughes et al, 2013;Rodayan et al, 2015), and these CECs were found to have 44 adverse effects on aquatic organisms (Gay et al, 2015;Kidd et al, 2007;Kümmerer, 2008;Purdom 45 et al, 1994). Discharges of wastewater treatment plants (WWTPs) have been identified as the 46 primary source for CECs introduced into surface waters (Luo et al, 2014).…”
mentioning
confidence: 99%
“…ECs include newly synthesized substances as well as ones that have long been present in the environment but whose presence and significance are only now being elucidated [3]. They include a wide array of different compounds and their transformation products: pharmaceuticals, personal care products, pesticides, veterinary products, industrial compounds/by-products, food additives, and engineered nano-materials [4][5][6][7][8][9][10]. An estimated 23 million chemicals have been indexed, with more than 7 million commercially available but only 230,000 are inventoried or regulated by governments worldwide [11].…”
Section: Introductionmentioning
confidence: 99%